ANALISIS SISTEM PERTUKARAN INFORMASI OTOMATIS DAN PERLINDUNGAN DATA NASABAH TERHADAP KETERBUKAAN DATA DAN INFORMASI PERBANKAN DAN PERPAJAKAN INDONESIA - Pajaria, Yusiresita; Gustiana, Iceu Sri (Sekolah Tinggi Ekonomi Dan Bisnis Islam Darussalam, 2019)
Abstract This study aims to identify and assess the implementation, to identify and provide legal protection for the community,  To find out how the public perception related to the enactment automatic information exchange system in Automatic Exchange System Of Information in banking and taxation in Indonesia. The method used is normative is a source of research is the literature data. The research is descriptive analytic waged a portrait of something with words or sentences, then separated categories for the conclusion. The approach taken is the approach of legislation and conceptual approaches. The research result of this thesis is that the Government Regulation in Lieu of Law No. 1 of 2017 on Access to Financial Information for the Interest Tax authority governing the confidentiality opening of access to finance, especially in the field of taxation and banking. Government Regulation in Lieu of Law derogation of this nature, the Government Regulation in Lieu of Law did not eliminate the presence of the General Provisions Act Taxation and the Banking Act rather run in tandem. However, when there are specific concerns regarding the opening of access to tax information that is regulated by government regulation in lieu of this Act, the regulations imposed specifically the Government Regulation in Lieu of Law No. 1 of 2017. The Government Regulation in Lieu of Law is not yet set in particular the protection of confidential data and customer information taxpayer. data privacy protection and customer information taxpayer still refers to the General Provisions Act Taxation. If the Directorate of Taxpayer act outside the authority of Government Regulation in Lieu of Law is, it can be subject to criminal sanctions were made on complaints of people who feel that their rights have been violated. Related to people's perceptions of these systems are still many people who know about these systems require further dissemination by the government.   Keywords: Secrets of bank, Tax, Automatic exchange system of information